2020
DOI: 10.31219/osf.io/ysrjk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Embodying Gender/sex Identity during Infancy: A Theory and Preliminary Findings

Abstract: In this paper we tried to loosen the following knot: at somepoint in mid toddlerhood, children evidence a gender/sex—a personal sense of group belonging which alsopredicts individual behaviors and wants—play, dress andpeer preferences. Yet at birth, although individual patterndifferences in embodied responses to new stimuli exist,these do not appear to correlate with gender/sex (Kagan,1994), and few measurable differences exist betweenfemale-designated and male-designated infants. As gender/sex becomes visible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…During this same time period mothers vocalized more to daughters than to sons (Sung et al, 2013). In a last example, another analysis showed that from months 3 to 6, mothers engaged in more gross motor activities with sons than with daughters and shifted sons from one position to another with greater frequency and duration than they did daughters (Fausto-Sterling et al, 2020).…”
Section: Phase 1: Dyad Interactionsmentioning
confidence: 96%
See 4 more Smart Citations
“…During this same time period mothers vocalized more to daughters than to sons (Sung et al, 2013). In a last example, another analysis showed that from months 3 to 6, mothers engaged in more gross motor activities with sons than with daughters and shifted sons from one position to another with greater frequency and duration than they did daughters (Fausto-Sterling et al, 2020).…”
Section: Phase 1: Dyad Interactionsmentioning
confidence: 96%
“…Gender/sex development bears the hallmarks of a dynamic system. In previous work, based on a review of developmental psychology literature, my colleagues and I divided gender/sex emergence into three phases (Fausto-Sterling, 2020;Fausto-Sterling et al, 2020). The first, which spans the period from birth (or before) through about 14 months, involves the acquisition of gender/sex recognition skills.…”
Section: The Phases Of Gender/sex Developmentmentioning
confidence: 99%
See 3 more Smart Citations